Acoustic Detection and Quantification of Fish in Lancang Waters of Seribu Islands, Indonesia - Purnawan, Syahrul; Manik, Henry M.; Manik, Agustina Sartika; Elson, La; Kang, Myounghee (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Sound propagates effectively through the water column, establishing hydroacoustic technology as a premier method for underwater exploration, including the mapping of aquatic ecological resources. While the fisheries sector is considered pivotal in aquatic resource studies, mapping fisheries remains challenging due to the distinct distribution patterns exhibited by fish within the water column, which are intricately linked to their habitat preferences. In this study, the hydroacoustic method was employed to analyze the distribution of fish in the waters surrounding Lancang Island, Seribu Islands, Jakarta.  This analysis utilized the target strength (TS) value alongside oceanographic parameters. Acoustic data was collected using a 200 kHz single beam echosounder based on parallel transects encircling the waters of Lancang Island. CTD was utilized to collect oceanographic data to acquire temperature and salinity profiles within the water column. The acoustic data processing was conducted using the post-processing software SONAR 5-pro. The analysis was performed based on acoustic cells, obtained by dividing segments every 100 m horizontally and layers every 5 m vertically, thereby obtaining the Target Strength per cell (TSc) and volume backscattering strength (SV) values from each cell. The results showed that the highest average TSc value was found in the depth range of 26-31 m at -46.98 dB, and the highest SED biomass was also found in the same depth range at 26.6 kg.ha-1. Based on the analysis of water temperature and salinity, it was found that these factors significantly influence the distribution of fish in the waters of Lancang Island (R-square= 0.1276 and P< 0.05). This finding also indicates the presence of other parameters affecting fish distribution in Lancang waters, with the type of substrate and habitat emerging as potential determining factors, notably in coral reef environments.